Improving the Performance of Polymer Inclusion Membranes in Separation Process Using Alternative Base Polymers: A Review - Fidelis Nitti; Odi Theofilus Edison Selan; Bosirul Hoque; David Tambaru; Muhammad Cholid Djunaidi (Indonesian Journal of Chemistry, 2022)
Polymer inclusion membrane (PIM) has recently evolved as an alternative separation technique to conventional solvent extraction as it eliminates the use of toxic solvents, reduces separation cost, and simplifies the separation process. PIM is the new generation of a liquid membrane made by casting solution containing liquid phases (extractant and plasticizer/modifier) and base polymers. Despite its better performance and stability in comparison to the previous types of liquid membranes, PIM's robustness for applications on an industrial scale is still considered insufficient mainly due to its limited stability in the long-term separation process. In recent years, different approaches have been devoted to improving the stability of PIM while maintaining its performance. This review aims to summarize and evaluate the current literature on the improvement of the performance of PIMs with particular focus on the use of alternative base polymers, including non-conventional linear homopolymers, copolymers, or cross-linking polymers. Furthermore, more emphasis is given to the composition, fabrication process, and application of the PIMs. Finally, the performance of the PIMs with the alternative base polymers in terms of extraction rate and long-term stability is presented and compared to the PIMs fabricated using their corresponding common base polymers.